2020
DOI: 10.1055/s-0040-1713154
|View full text |Cite
|
Sign up to set email alerts
|

Association between rs1421085 and rs9939609 Polymorphisms of Fat Mass and Obesity-Associated Gene with High-Density Lipoprotein Cholesterol and Triglyceride in Obese Turkish Children and Adolescents

Abstract: Several studies have shown that rs9939609 and rs1421085 in fat mass and obesity-associated (FTO) gene rs17782313 and rs12970134 in melanocortin-4 receptor (MC4R) gene influence obesity. In the present study, we aimed to determine association between rs9939609, rs1421085, rs17782313, and rs12970134 polymorphism, and their relation with body mass index (BMI), glucose, insulin, homeostasis model assessment of insulin resistance (HOMA-IR) and lipid values in obese children. We included 100 newly diagnosed obese ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
6
0
2
Order By: Relevance
“…In our results, variant rs1421085 was found to be associated with high consumption of Kcal, and mean differences were observed in the percentage of body fat. This marker has been extensively studied, and recent studies have found higher allelic frequencies in people with obesity as well as its associations with higher triglyceride and cholesterol levels in Turkish children [31]. Likewise, rs1421085 was previously reported with higher allelic frequencies in the Iranian population, showing its association with obesity markers [32].…”
Section: Discussionmentioning
confidence: 84%
“…In our results, variant rs1421085 was found to be associated with high consumption of Kcal, and mean differences were observed in the percentage of body fat. This marker has been extensively studied, and recent studies have found higher allelic frequencies in people with obesity as well as its associations with higher triglyceride and cholesterol levels in Turkish children [31]. Likewise, rs1421085 was previously reported with higher allelic frequencies in the Iranian population, showing its association with obesity markers [32].…”
Section: Discussionmentioning
confidence: 84%
“…По данным нашего исследования, в общей группе обнаружена ассоциация с содержанием ХС ЛПНП (наименьший уровень ХС ЛПНПу носителей генотипа АТ, достоверно больший -у подростков с генотипом АТ). У молодых людей 25-35 лет из популяции города Новосибирска самая высокая концентрация ХС ЛПНП также наблюдалась у носителей генотипа АА [7], тогда как у детей в Турции rs9939609 ассоциирован с ХС ЛПВП и ТГ [4]. Кроме того, статистически значимые различия у носителей разных генотипов rs9939609 гена FTO выявлены по средней толщине кожной складки в средней трети правого плеча (р = 0,049; наибольшая при генотипе АА) у девочек.…”
Section: Discussionunclassified
“…Число детей и подростков с ожирением за последние 20 лет увеличилось в 2 раза. Важным фактором риска его развития является генетическая предрасположенность [1][2][3][4]. В онлайн-каталоге генов и генетических заболеваний человека OMIM (Online Mendelian Inheritance in Man) при поиске по ключевому слову «obesity» находится 738 записей [5].…”
Section: Introductionunclassified
“…They also suggested the possibility of an allele-dependent effect of the rs9939609 polymorphism on serum TG levels. Inandiklioğlu et al demonstrated that the serum TG levels increased with the TT, TA, and AA genotypes of the rs9939609 polymorphism in a group of obese Turkish children and adolescents aged 3–17 years, in that order (1.21 vs. 1.37 vs. 1.89 mmol/L, p = 0.004) [ 127 ]. A similar finding was obtained in a study on a group of south Brazilian children and adolescents [ 53 ].…”
Section: Some Genetic Polymorphisms Of Fto Increas...mentioning
confidence: 99%